Editing of Mitochondrial Transcripts nad3 and cox2 by Dek10 Is Essential for Mitochondrial Function and Maize Plant Development - Qi, Weiwei (Genetics, 2017)
Respiration, the core of mitochondrial metabolism, depends on the function of five respiratory complexes. Many respiratory chain-related proteins are encoded by the mitochondrial genome and their RNAs undergo post-transcriptional modifications by nuclear genome-expressed factors, including pentatricopeptide repeat (PPR) proteins. Maize defective kernel 10 (dek10) is a classic mutant with small kernels and delayed development. Through positional cloning, we found that Dek10 encodes an E-subgroup PPR protein localized in mitochondria. Sequencing analysis indicated that Dek10 is responsible for the C-to-U editing at nad3-61, nad3-62, and cox2-550 sites, which are specific editing sites in monocots. The defects of these editing sites result in significant reduction of Nad3 and the loss of Cox2. Interestingly, the assembly of complex I was not reduced, but its NADH dehydrogenase activity was greatly decreased. The assembly of complex IV was significantly reduced. Transcriptome and transmission electron microscopy (TEM) analysis revealed that proper editing of nad3 and cox2 is critical for mitochondrial functions, biogenesis, and morphology. These results indicate that the E-subgroup PPR protein Dek10 is responsible for multiple editing sites in nad3 and cox2, which are essential for mitochondrial functions and plant development in maize.